ANALISIS DIMENSI KUALITAS PELAYANAN PASIEN RAWAT INAP BPJS DI RUANG TULIP RUMAH SAKIT UMUM DAERAH (RSUD) DJOJONEGORO KABUPATEN TEMANGGUNG - Ibrahim, Muh Ihsan; Yuniningsih, Tri (Journal of Public Policy and Management Review, 2016)
Public service is considered satisfying and brings satisfactory when the service comes to fulfill the society’s needs and demands. When the society doesn’t feel satisfy by the given service, it can be concluded that the given service doesn’t meet its quality and efficiency. To assess whether a public service provided in a good quality or not, the researcher uses the five dimensions measuring the quality of service by Zeithaml, et.al. The present research aims at describing and analyzing the BPJS public service opname patient at Tulip Room at Tulip Room in RSUD Temanggung Regency. The analysis can be seen from the dimensions of physical evidence, reliability, responsiveness, assurance, and empathy. The study deploys qualitative descriptive method by recruiting 7 informants. The informants are the BPJS opname patients. The result of the study showed that the quality of healthy public service at Tulip Room at Tulip Room in RSUD Temanggung Regency is optimal. It can be seen from the scheduled appropriate time of service, the responsive response to the patients by the staff, a good security service, and respecting the patients’ priority. From the research, it can be recommended that to increase the hospitality at Tulip Room in RSUD Temanggung Regency, the hospital is in need of a set of security cover to enhance the patients’ convenience by the noisy from inside and outside the Tulip Room that are in under renovation. In addition, to increase public participation, an information board is needed where the society can give complaints and suggestions to a better quality of the hospital and keep updating the information on the information board.